The sign of the seahorse : a tale of greed and high adventure in two acts - Base, Graeme (New York : H.N. Abrams, 1992)
The inhabitants of a coral reef are threatened when a shady real estate deal started by the greedy Groper floods their area with poisonous waste.
Keywords: Marine animals -- Fiction; Marine pollution -- Fiction; Pollution -- Fiction